Critical Study of the Results of Hawking’s Theory of Unity in Physics Based on Mullā Ṣadrā’s Graded Unity - Ahmad Mansouri Matak (Gilani); Fahimeh Shariati; Seyed Majid Saberi Fathi; Muhammad Javad Enayati Rad (آموزه‌‌های فلسفه اسلامي, 2021)
Stephen Hawking, a contemporary theoretical physicist, considered the discovery of a unifying theory in physics to be very effective and he claims the existence of the theory of great unity by claiming the three possibilities. He considers the works and benefits of ontology such as; the possibility of recognizing and describing the laws governing the universe, knowing how the extreme small universe works at the beginning of creation, answering questions about the beginning, the cause of creation, and the role of God as the Creator of the universe for the theory of unity. The metaphysical results and implications of the theory of unity in this article are extracted and examined in a comparative way with the graded unity theory of Mullā Ṣadrā. The graded unity of existence has a significant impact on ontology as well as philosophical epistemology and is a factor for linking sciences with each other, explaining the relationship between the parts of the universe, analyzing human’s liberty without contradicting the divine will, explaining the beginning of the world and answering other ontological ambiguities. It is shown in this research that Hawking’s philosophical questions can be answered with Mullā Ṣadrā’s theory of unity of existence.